ADHD: Systematic review of the beneficial effects of motor activity - Valentini, Manuela; Canini, Arianna (Formazione & insegnamento, 2020)
The increasing percentage of children diagnosed with ADHD represents a large body of students coping with poor motor coordination, behavior and attention problems, which results in compromised social relations. Traditional treatments include pharmaceutics with cognitive-behavioral and parental therapies. However, recently researchers have been investigating the influence of physical activity on the main deficits of children with ADHD. The primary objective of this review is to summarize the research that examined the effects of exercise by combining keywords such as: ADHD, sports, benefits, symptoms. Although studies varied by sample size, type of activity, and indexes analysed, results are significantly positive overall with improvement of symptoms, executive functions, and social interactions.